Experiments to enhance post-fire aspen seedling survival and growth - Larissa L. Yocom; Mark R. Kreider; Owen T. Burney; Tammy Parsons; Ryan T. Choi; Emily K. Liese; Karen E. Mock (New Forests, 2025)
Aspen forests provide wildlife, watershed, and aesthetic value, and the potential for reduced fire occurrence, behavior, and severity. There is interest in planting aspen to achieve various management objectives. However, few studies have investigated the optimal conditions for aspen seedlings in the western US. We conducted two experiments to address this knowledge gap. First, we tested the effects of shading structures (i.e., logs) and biochar on the survival and growth of 960 outplanted aspen seedlings in three exclosures in a recent fire footprint. Second, we tested whether experimentally placing logs near 120 naturally-occurring post-fire aspen seedlings affected survival or growth. Survival of outplanted seedlings was high (66%) despite hot and dry conditions in the years of the study. Logs and biochar had minimal effects on planted seedling survival and growth, but in one exclosure, survival of planted seedlings was lower in log and log + biochar treatments, likely due to the protection logs provided to small mammalian herbivores. Survival was higher for naturally-occurring seedlings with logs placed on the south side compared to control seedlings in one site, and growth was higher for naturally-occurring seedlings with a nearby log, but not significantly so. In sites where aspen seedling survival and growth are relatively robust, management actions to modify the microsite may not be necessary.